1993
DOI: 10.1083/jcb.120.3.757
|View full text |Cite
|
Sign up to set email alerts
|

Loss of epithelial differentiation and gain of invasiveness correlates with tyrosine phosphorylation of the E-cadherin/beta-catenin complex in cells transformed with a temperature-sensitive v-SRC gene.

Abstract: Abstract. Loss of histotypic organization of epithelial cells is a common feature in normal development as well as in the invasion of carcinomas. Here we show that the v-src oncogene is a potent effector of epithelial differentiation and invasiveness. MDCK epithelial cells transformed with a temperature-sensitive mutant of v-src exhibit a strictly epithelial phenotype at the nonpermissive temperature for pp60 .... activity (40.5~ but rapidly loose cell-to-cell contacts and acquire a fibroblast-like morphology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

41
632
3
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 862 publications
(678 citation statements)
references
References 61 publications
41
632
3
2
Order By: Relevance
“…Rhodamine-phalloidin staining did not reveal actin ®bers in ras-transformed Rat1 derivatives (Figure 2b). These changes were similar to those characteristic of oncogene-induced morphological transformations of other epithelial and ®broblastic cell lines (Schenenberger et al, 1991;Behrens et al, 1993).…”
supporting
confidence: 81%
“…Rhodamine-phalloidin staining did not reveal actin ®bers in ras-transformed Rat1 derivatives (Figure 2b). These changes were similar to those characteristic of oncogene-induced morphological transformations of other epithelial and ®broblastic cell lines (Schenenberger et al, 1991;Behrens et al, 1993).…”
supporting
confidence: 81%
“…MCF-7 were also cultured under growth factor-free, estrogen-free and hypoxic conditions using the OXOID incubator chamber (Basingtoke, Hamshire, England). The MDCKts.src cell line established after stable transfection of MDCK cells with a thermosensitive mutant of v-src (Behrens et al, 1993) was maintained in DMEM containing 10% FCS. (Emami et al, 2001) and the lipofectAMINE plus reagent (Invitrogen, Cergy-Pontoise, France).…”
Section: Cell Lines and Culture Conditionsmentioning
confidence: 99%
“…For confocal microscopy, cells grown on plastic or on collagencoated glass coverslips were fixed with 4% paraformaldehyde, quenched with 50 mM NH 4 Cl in PBS for 30 min, permeabilized in saponin 0.2% for 20 min, and then incubated in blocking solution (PBS, 1% BSA, 0.2% saponine) for 30 min. For single labeling of E-cadherin, MUC1, MUC5AC or the heparan-sulfate moiety of proteoglycans, respectively, HECD1 (1/400), 214D4 (1/3), 21M1 (1/250) and HepSS-1 (1/50) in PBS/1% BSA/0.2% saponin were added overnight.…”
Section: Confocal Microscopymentioning
confidence: 99%
“…2 Studies in cancer cell lines have shown that changes in the structure or in the expression of the components of the E-cadherin/␤-catenin complex result in the suppression of cell-cell adhesion and in the expression of an invasive phenotype. [3][4][5][6][7][8] In cancer, the maintenance of the epithelia is lost and dissociation of cells is associated with metastatic dissemination. This phenomenon can occur through a decrease in the expression level of E-cadherin and, regarding colon cancer, such decrease has been related to the tumor grade and clinical outcome.…”
mentioning
confidence: 99%